Phacoemulsification Alone versus Phacoemulsification Combined with Trabeculectomy for Primary Angle-Closure Glaucoma - Rhiu, Soolienah (Yonsei University College of Medicine, 2010)
Surgical outcomes of phacoemulsification only and phacoemulsification combined with trabeculectomy were compared in patients with primary angle-closure glaucoma (PACG). Clinical records of 41 consecutive patients were retrospectively reviewed, and there was no difference in best-corrected visual acuity and intraocular pressure preoperatively and at the final follow-up in both study groups. Regarding the number of anti-glaucoma medications, it was higher in the phacoemulsification combined with trabeculectomy group preoperatively than the phacoemulsification only group (p = 0.045), but both groups were taking similar quantities of medication at the final follow-up (p = 0.6). In addition, postoperative hypotony (two cases) occurred only after phacoemulsification combined with trabeculectomy, but not after phacoemulsification only. In one case after phacoemulsification only, a second operation was needed. There were no additional postoperative complications. In conclusion, both phacoemulsification only and phacoemulsification combined with trabeculectomy showed good surgical outcomes in PACG patients. Both procedures might be equally effective in treating patients with PACG.